Induction effect of chitosan on suppression of tomato early blight and its physiological mechanism - LIAO Chun-yan; MA Guo-rui; HONG Wen-ying (浙江大学学报. 农业与生命科学版)
Resistance to early blight of the tomato plants was induced by chitosan (1 mg/mL) at the fourth-leaf stage of seedlings. Chitosan treatment of tomato leaves before inoculation reduced the rates of diseased leaf and disease index. The relative efficiencies of resistance in cultivars were Hezuo908(highly resistant), Hezuo903 (moderately resistant), and Zaofeng (least resistant). As a consequence of the treatments, the activities of peroxidase (POD), polyphenol oxidase (PPO), phenylalanine ammonia lyase (PAL), chitinase, and β-1, 3-glucanase in tomato leave increased but in different degrees with different cultivars. The time courses of change in enzyme activities following chitosan treatment were also different. The mechanism of induced resistance of chitosan was disscussed.